POTENTIAL ANTIFUNGAL ACTIVITY OF DIFFERENT HONEY BRANDS FROM PAKISTAN: A QUEST FOR NATURAL REMEDY - Ahmad, Kafeel; Khalil, Ali Talha; Somayya, Ramla; Khan, Faisal Nouroz; Shah, Ali Raza; Ovais, Muhammad; Shinwari, Zabta Khan (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Besides a wholesome food, honey is known for its therapeutic implications. We investigated the antifungal activity of five honeys of different types from Pakistan against various pathogenic fungal strains. Antifungal properties of processed and non-processed honey were determined. Materials and Methods: The antifungal assay of honey was carried out against Aspergillus niger, Aspergillus flavus, Aspergillus fumigates, Alterneria alternata, Fusarium solanai, Microsporum canis, Penicillium funiculosium and Rhizopus solanai. Different dilutions of honey samples were used (20%, 50%, 70%, 90% and 100% w/v so as to find out the minimum effective concentration of each honey type. Results: It was observed that all of the honey samples were highly active, with percent inhibition range of (3-81%) for Aspergillus niger, (2-82%) for Aspergillus flavus, (1-76%) for Aspergillus fumigates, (1-84%) for Alterneria alternata, (2- 67%) for Fusarium solanai, (1-87%) Microsporum canis, (2-78%) Penicillium funiculosium and (1-86%) for Rhizopus solanai. Conclusion: The study of Pakistani honey brands reveals that they possess a substantial antifungal nature. Therefore, they may be used in curing fungal infections along with antifungal drugs as a cheaper alternative natural remedy with no side effects.